The Pastoureaux of 1320 - Barber, Malcolm (The journal of ecclesiastical history, 1981)
The rising in France in 1320 known as the Pastoureaux, or Shepherds' Crusade, receives little attention in most histories, and it is, indeed, a relatively small-scale event for which there are limited sources. Nevertheless, it has wider implications than have been generally recognised. The purpbse of this paper is therefore two fold: to describe these events through khe available sources and to offer some ideas concerning their historical! importance.